THE INCIDENCE OF PATIENTS DISCHARGING AGAINST MEDICAL ADVICE (AMA) AS INFLUENCED BY SERVICE QUALITY AND MEDIATED BY PATIENT SATISFACTION - Stefanie, Nadia Cecilia; Tj, Hery Winoto; Saparso, Saparso (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The purpose of this study was to examine and analyze the influence of patient satisfaction and service quality on the incidence of APS patients returning home, the influence of service quality on patient satisfaction, and the influence of patient satisfaction mediating the influence between service quality on the incidence of APS patients returning home. This type of research is causal associative research. Causal associative research is research that aims to determine the influence or relationship between two or more variables, which are causal and one variable (independent) affects the other variable (dependent). Based on the results obtained in this study, it can be concluded that: patient satisfaction affects APS patients returning home. The incidence of APS patients returning home will decrease if patient satisfaction increases; Service quality affects APS patients returning home. The incidence of APS patients returning home will decrease if the quality of service provided improves; Service quality affects patient satisfaction. Patient satisfaction will increase if the quality of service improves; Patient satisfaction is able to mediate the influence of service quality on APS patients returning home. Patient satisfaction plays a role in the quality of service for APS patients returning home.